2022
DOI: 10.14336/ad.2021.1110
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-derived Exosomal MicroRNA as Therapy for Vascular Age-related Diseases

Abstract: Vascular age-related diseases describe a group of age-related chronic diseases that result in a considerable healthcare burden to society. Vascular aging includes structural changes and dysfunctions of endothelial cells (ECs) and smooth muscle cells (SMCs) in blood vessels. Compared with conventional treatment for vascular age-related diseases, stem cell (SC) therapy elicits better anti-aging effects via the inhibition/delay ECs and SMCs from entering senescence. Exosomal noncoding RNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…SCEVs, including those from mesenchymal stromal cells (MSCEVs), are recognized for their rich miRNA composition, which varies depending on the cell type and microenvironment. The active accumulation of miRNA cargo within vesicles can influence recipient cells suggesting dedicated biological roles of these EVs [ 117 , 118 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…SCEVs, including those from mesenchymal stromal cells (MSCEVs), are recognized for their rich miRNA composition, which varies depending on the cell type and microenvironment. The active accumulation of miRNA cargo within vesicles can influence recipient cells suggesting dedicated biological roles of these EVs [ 117 , 118 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…MicroRNA, a predominant component in hBMSC-sEV, is a type of noncoding RNA with a short, singlestranded that target mRNA sequences by binding the 3′-untranslated regions (3′-UTR), which causes degradation or translation blockade of mRNA [14][15][16][17][18]. Previous studies have shown that the miRNA could regulate and affect a variety of cell function, such as proliferation, invasion, inflammation responses and apoptosis [19][20][21]. A series of miRNAs have been revealed their association with osteogenesis, which participated in the process of bone remodeling, and presented a critical role in the progression of tendon homeostasis and osteoarthritis [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…10 Recent data demonstrate that exosomes derived from osteoblasts, MSCs, osteoclasts and macrophages have therapeutic potential in osteoporosis and regenerative medicine. 4,11,12 Osteoblasts have been shown to communicate with other cell phenotypes through secretion of exosomes 13 and exosome-derived microRNAs exhibit a potential to direct osteogenesis and osteoclastogenesis. 14,15 However, there is a gap in the literature regarding the effects of preosteoblast-derived exosomes on bone marrow macrophages and bone remodelling dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…They offer therapeutic advantages including biocompatibility, reduced immunogenicity and transportation of cargo contents without degradation due to the nature of the exosome bilipid capsule 10 . Recent data demonstrate that exosomes derived from osteoblasts, MSCs, osteoclasts and macrophages have therapeutic potential in osteoporosis and regenerative medicine 4,11,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation